PENGARUH WORD OF MOUTH, MEDIA SOSIAL DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN DI DAPOER MBOK SUM KEDIRI - Amalia Qatrunnada Al Faranandi; Irra Chrisyanti Dewi (ITB AAS Indonesia Surakarta, 2026)
Dapoer Mbok Sum Kediri is the target of this research, which intends to investigate how customers' perceptions of quality, social media, and word of mouth impact their purchasing choices. We used a quantitative approach and surveyed 178 people using a purposive sample method to compile our results. Using SmartPLS 4.0 software, the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach was used to analyze the data collected from a Likert-scale questionnaire that served as the study instrument. All three independent variables—perceived quality, word of mouth, and social media—had a favorable and statistically significant impact on consumers' final purchasing choices. The fact that both the t-statistic and the p-value are more than the crucial threshold and less than the significance level proves this. A t-statistic of 7.546 indicates that, among the factors, perceived quality has the greatest impact. In addition, the R-squared value indicates that the study model well explains the observed variance in consumers' purchasing choices. This research lends credence to the idea that human interaction and the use of social media as a means of disseminating information play a significant role in shaping consumers' perceptions of the quality of products and services on offer. Consequently, it is recommended that business practitioners keep the quality of their products and services constant while maximizing the effectiveness of their marketing efforts via the use of digital platforms and suggestions. This will increase customer interest and ultimately, purchase choices.